1970
DOI: 10.1017/s0021859600022863
|View full text |Cite
|
Sign up to set email alerts
|

Moisture, its accumulation and site of evaporation in the coats of sweating cattle

Abstract: SUMMARYMoisture content of the coats of cattle, expressed as the percentage of the dry weight of hair, has been measured in a wide variety of environmental conditions in summer, springand winter. Strips of coat were clipped from 25 Jersey, 15 Zebu x Jersey crossbred and 9 Hereford heifers in a shed, in a climate room under warm, hot dry and hot humid conditions and outdoors both in sun and shade. Moisture content, weight of coat per unit area, depth of coat, skin and rectal temperatures, sweating and respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 14 publications
(11 reference statements)
1
12
0
1
Order By: Relevance
“…At high humidities, water (Allen et al 1970) or water vapour (Finch 1985) may be trapped in the air spaces between the hairs of Bus taurus coats, and because of the reduced evaporation there is a compensatory rise in sweating rate.…”
Section: Cattle Coat Characteristicsmentioning
confidence: 99%
“…At high humidities, water (Allen et al 1970) or water vapour (Finch 1985) may be trapped in the air spaces between the hairs of Bus taurus coats, and because of the reduced evaporation there is a compensatory rise in sweating rate.…”
Section: Cattle Coat Characteristicsmentioning
confidence: 99%
“…G. pallidipes and other savannah species exploit mainly mammals to obtain a blood meal [28,29]. These hosts lose heat and water through their skin [21], creating a humidity gradient between the skin and the environment [20,30,31], equipping these animals with a means of regulating body temperature through evaporation. Indeed, water droplets are formed by aprocrine glands during sweating [32] indicating that the humidity is close to saturation in the air near the skin (>90% at 37°C, 57 hPa).…”
Section: Discussionmentioning
confidence: 99%
“…The relative humidity in the cattle coat is influenced by both temperature of the hair and vapour pressure (Allen et al 1970). The moisture content of the cattle coat can range from 5.8 to 27.5% and this can be influenced by the cattle breed and environmental factors (Allen et al 1970). The study also indicated that in hot environments the relative humidity of the cattle coat could be up to 5.5% above the average moisture content.…”
Section: Coat Humiditymentioning
confidence: 92%
“…However, it is now believed that the relative humidity of the microenvironment is more critical than the ambient relative humidity with regards to mortality (Inglis et al 2001). The relative humidity in the cattle coat is influenced by both temperature of the hair and vapour pressure (Allen et al 1970). The moisture content of the cattle coat can range from 5.8 to 27.5% and this can be influenced by the cattle breed and environmental factors (Allen et al 1970).…”
Section: Coat Humiditymentioning
confidence: 99%